Engaging with Carol Bacchi. Strategic Interventions and Exchanges - Bletsas, Angelique; Beasley, Chris (University of Adelaide Press, 2012)
This book illuminates, commemorates, and builds upon Bacchi's 'WPR' approach. It outlines the trajectory of the development of the 'WPR' approach from Bacchi's early engagements with feminist thinking, as an academic in scholarly environments which were often the preserve of men, towards the theoretical sophistication of an approach which requires an ongoing critical assessment of assumptions about the social world, social 'problems', policy agendas deemed to respond to those 'problems', and the researcher's positioning. This book arose out of a conference organised by the Fay Gale Centre for Research on Gender at The University of Adelaide honouring Carol Bacchi's work and is intended to make that work accessible to a range of audiences.